
Solve the system of equations:
y=x^2 + 9
y=6x

Solve the system of equations:
y=4x+8
x^2 + 7x  20


Y = x^2 + 9.
Y = 6x.
In Eq1, replace Y with 6x:
6x = x^2 + 9.
x^2  6x + 9 = 0.
Solve the Quadratic Eq .

So wait would x^2  6x + 9 = 0 be the answer for number 1?

Y = 4x + 8.
Y = x^2 + 7x  20.
In Eq2, replace Y with 4x + 8:
4x + 2 = x^2 + 7x  20.
x^2 + 3x  22 = 0.
Solve using Quadratic Formula:
X = (B + sqrt(B^24AC))/2A.
X = (3 + sqrt(9 + 88))/2 = 3.42, and 6.42.


1.x^2  6x + 9 = 0.
Solve the Eq. by factoring:
9 = 3 * 3.
(x3) (x3) = 0,
x3 = 0, X = 3.
3 should satisfy both of your given Eqs.